2021
DOI: 10.1038/s43247-021-00305-5
|View full text |Cite
|
Sign up to set email alerts
|

Precession cycles of the El Niño/Southern oscillation-like system controlled by Pacific upper-ocean stratification

Abstract: Modern observations have presented linkages between subsurface waters of the western Pacific warm pool and both El Niño/Southern Oscillation-related and extratropic-controlled upper-ocean stratification on interannual timescales. Moreover, studies have showed that such controls may operate on orbital cycles, although the details remain unclear. Here we present paired temperature and salinity reconstructions for the surface and thermocline waters in the central western Pacific warm pool over the past 360,000 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
4
14
0
Order By: Relevance
“…(2020). The conversion from Mg/Ca to temperature for Core KX97322‐4 (Zhang et al., 2021) is different from our method. It uses the equation developed by Hollstein et al.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…(2020). The conversion from Mg/Ca to temperature for Core KX97322‐4 (Zhang et al., 2021) is different from our method. It uses the equation developed by Hollstein et al.…”
Section: Discussionmentioning
confidence: 74%
“…The two cores are both located in the main outflow pathway of the ITF in the eastern Indian Ocean. To understand the heat transport processes of the ITF from the western Pacific to the eastern Indian Ocean during the last 160 Kyr, we compared the SSTs of Core MD98-2172 and Core MD77-150 with data from Core KX97322-4 (Zhang et al, 2021) and Core MD06-3067 (Bolliet et al, 2011) in the western equatorial Pacific Ocean in the core region of the IPWP. Core MD06-3067 is located to the south of Mindanao, the main entrance area for the ITF (Figures 1 and 7, Figure S2 in Supporting Information S1).…”
Section: Glacial-interglacial Changes Of Sst Gradient Along the Itf P...mentioning
confidence: 99%
“…2d ), the overturning circulation that mainly formed in winter by intense vertical mixing 72 was warmed due to the rising insolation in austral winter (Fig. 2e ), and this warmer signal was further transferred to the western Pacific 69 . Preceding thermocline anomalies in the western and central deep tropical Pacific contribute to the recharge phase of ENSO 63 , 73 , and modern observations also indicate that the change in the WPWP OHC is tightly related to ENSO activity 74 .…”
Section: Resultsmentioning
confidence: 97%
“…A continuous subduction of the extratropical warm anomaly to the WPWP thermocline is hypothesized to affect ENSO-like transitions since 360 ka, paced by orbital precession 69 . The results of earlier modeling simulations have shown that orbital precession exerts a major impact on ENSO-like processes through the strength of ocean-atmosphere feedbacks 70 , 71 .…”
Section: Resultsmentioning
confidence: 99%
“…Today this scenario occurs as an irregular periodic variation along with an opposite "La Niña" state in the tropical Pacific, with strong trade winds and more intense upwelling in the eastern tropical Pacific driving increased productivity on interannual to decadal timescales. Changes in the mean state over longer timescales can be recorded in deep-sea sediment archives (e.g., Pena et al, 2008;Zhang et al, 2021). The large range of variations in our carbon export record in the tropical Pacific (XRF-Ba elemental intensities and benthic foraminiferal accumulation rates) during the Maastrichtian greenhouse argues against the hypothesis of a continual or permanent El Niño-like state.…”
Section: Direct Response To Precession During Greenhousementioning
confidence: 94%